Pemanfaatan Serabut Gambas (Luffa Cylindrica) Sebagai Template Untuk Pembuatan Scaffold Hidroksiapatit - Lubis, Apriadi; Fadli, Ahmad; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Utilization of hydroxyapatite (HA) as a bone implant could be done by making the HA in the form of a scaffold to obtain good porosity and good mechanical strength. The purpose of this research is to determine the influence of solid loading HA toward characters of scaffold HA fabricated by polymeric sponge method. Gambas sponges were cut into circular samples of 1 cm diameter and then soaked with distilled water for 12 hours and then dried in the open air for 1 hour. Gambas sponges were then impregnated with a slurry made by mixing 10; 11; and 12 grams of HA, 10% sago, 3% Darvan 821A and 12 grams of distilled water. The mixture were stirred for 20 hours to form a slurry. The substrates were impregnated and then dried at 110oC for 3 hours. The resulting green bodies then burned at 600oC for 1 hour and followed by sintering at 1250oC for 1 hour. The results showed that the addition of HA lead to smaller shrinkage and porosity. In addition of HA, the resulting shrinkage in the range of 57,71-59,46%, porosity 52,30-56,37%, and compressive strength 5,14-7,88 MPa.Keywords: hydroxyapatite, luffa cylindrica, polymeric sponge, scaffold